Dimensions of Object Relations in People with Autism Spectrum Disorder as a Basis for Strengthening Social Relatedness Skills - Simona Rogič Ožek (Center for Educational Policy Studies Journal)
This paper presents the results of a study focusing on the dimensions of object relations in people with autism spectrum disorder. An object relation denotes a relationship with a significant other, within which several identification processes take place through a meaningful emotional exchange. This is described by the developmental process of separation and individuation, which primarily occurs in children from birth to their third year of life. Although deficits in social relationships represent the most typical features of autism, there is still a great deal of uncertainty in this field. Based on the theoretical background, we hypothesised that differences in the characteristics of object relations in people with autism spectrum disorder compared to the characteristics of object relations in people without autism spectrum disorder are reflected in a greater expression of disturbances in object relations, especially in the more pronounced dimensions of greater social isolation and symbiotic merging. The quantitative research sample comprised 38 adults with autism spectrum disorder with normal intellectual abilities and 100 adults without autism spectrum disorder. The Test of Object Relations, which measures the individual dimensions of object relations, was used for data collection. The results show that there are statistically significant differences between the two groups of respondents, as the dimensions of symbiotic merging, social isolation and separation anxiety are more pronounced in adults with autism spectrum disorder. These findings serve as a basis for designing professional support for people with autism spectrum disorder in order to promote autonomy to strengthen the skills needed for social relatedness and social inclusion.